2019
DOI: 10.1039/c9ra00715f
|View full text |Cite
|
Sign up to set email alerts
|

Silyl diol ester as a new selectivity control agent in MgCl2-supported Ziegler–Natta systems for propylene polymerization: catalyst structure and polymer properties

Abstract: In this study, bis(benzoyloxy)dimethylsilane (SDE) was developed as a non-phthalate selectivity control agent (internal donor (ID) and external donor (ED)) in MgCl 2 -supported Ziegler-Natta (ZN) systems. The impact of SDE as an ID was investigated in regards to chemical composition, morphology, adsorption behavior (using FTIR spectroscopy, WAXD and SEM studies) and the propylene polymerization performance of the catalyst. The results of the adsorption behavior of SDE revealed that SDE, while able to stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Another study on SDE revealed that catalytic activity increases with increase in Mg/SDE ratio and reaches to a maximum at a particular Mg/SDE [106]. The similar phenomenon was noted for II too.…”
Section: Silyl Diol Esterssupporting
confidence: 59%
“…Another study on SDE revealed that catalytic activity increases with increase in Mg/SDE ratio and reaches to a maximum at a particular Mg/SDE [106]. The similar phenomenon was noted for II too.…”
Section: Silyl Diol Esterssupporting
confidence: 59%
“…The n -heptane solvent was refluxed with metal sodium and benzophenone for 24 h and then was distilled out before use. The bis­(methoxymethyl)­silanes were prepared according to the literature , with a little modification. Dimethoxydiphenylsilane (Donor-Ph), diisopropyldimethoxysilane (Donor-P), and dicyclopentyldimethoxysilane (Donor-D) were purchased from Innochem.…”
Section: Methodsmentioning
confidence: 99%
“…Bis­(methoxymethyl)­silanes were prepared according to the previously reported procedure with some modifications. , In a typical example, the synthesis of bis­(methoxymethyl)­silanes (Donor-PhS, Donor-PS, and Donor-DS) was carried out as follows (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…These polymers are commercially produced mostly by heterogeneous Ziegler Natta catalysts 4,12,13 . These catalysts are mainly composed of support (MgCl 2 , Mg(OEt) 2 , and silica) and TiCl 4 as active center, and occasionally electron donor to control isotacticity in polypropylene 14–18 . By the heterogenization of catalyst on the carrier, its activity and morphology are regulated, which diminishes reactor foaling and improves solid particles conveying in industrial reactors, respectively 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…4,12,13 These catalysts are mainly composed of support (MgCl 2 , Mg(OEt) 2 , and silica) and TiCl 4 as active center, and occasionally electron donor to control isotacticity in polypropylene. [14][15][16][17][18] By the heterogenization of catalyst on the carrier, its activity and morphology are regulated, which diminishes reactor foaling and improves solid particles conveying in industrial reactors, respectively. 19,20 Among the mentioned supports, MgCl 2 is the most appreciated one, due to its abundance, cheap price and ease of preparation methods.…”
Section: Introductionmentioning
confidence: 99%